The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/nar/gki639
|View full text |Cite
|
Sign up to set email alerts
|

The XPF-ERCC1 endonuclease and homologous recombination contribute to the repair of minor groove DNA interstrand crosslinks in mammalian cells produced by the pyrrolo[2,1-c][1,4]benzodiazepine dimer SJG-136

Abstract: SJG-136, a pyrrolo[2,1-c][1,4]benzodiazepine (PBD) dimer, is a highly efficient interstrand crosslinking agent that reacts with guanine bases in a 5′-GATC-3′ sequence in the DNA minor groove. SJG-136 crosslinks form rapidly and persist compared to those produced by conventional crosslinking agents such as nitrogen mustard, melphalan or cisplatin which bind in the DNA major groove. A panel of Chinese hamster ovary (CHO) cells with defined defects in specific DNA repair pathways were exposed to the bi-functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 35 publications
6
61
0
Order By: Relevance
“…We also performed time-course experiments using both the comet assay and the Annexin V assay to establish the kinetics of the DNA crosslinking and apoptosis induction in primary CLL cells. In keeping with previous findings (Clingen et al, 2005), SJG-136 rapidly induced DNA crosslinks and these were maximal after 24 h exposure (data not shown). Apoptosis was also induced in a time-dependent manner with clear evidence of enhanced apoptotic cell killing in the cultures exposed to the combination of SJG-136 and fludarabine ( Figure 1D).…”
Section: Sjg-136-induced Dna Iclsupporting
confidence: 93%
See 3 more Smart Citations
“…We also performed time-course experiments using both the comet assay and the Annexin V assay to establish the kinetics of the DNA crosslinking and apoptosis induction in primary CLL cells. In keeping with previous findings (Clingen et al, 2005), SJG-136 rapidly induced DNA crosslinks and these were maximal after 24 h exposure (data not shown). Apoptosis was also induced in a time-dependent manner with clear evidence of enhanced apoptotic cell killing in the cultures exposed to the combination of SJG-136 and fludarabine ( Figure 1D).…”
Section: Sjg-136-induced Dna Iclsupporting
confidence: 93%
“…Importantly, this appears to be more marked in CLL cells when compared to normal lymphocytes (Moufarij et al, 2006). In addition, Clingen et al (2005) demonstrated that sensitivity to SJG-136 was dependent to some extent on ERCC1 expression in CHO cells. To determine whether ERCC1 was induced by SJG-136 in primary CLL cells, we performed real-time RT-PCR on RNA extracted from CLL cells exposed to SJG-136, fludarabine and both drugs in combination.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The cytotoxicity of these molecules is thought to be directly related to the formation of interstrand cross-links (in this instance at Pu-GATC-Py sites [22,23]), and members of the PBD dimer class are now being used as payloads for antibody-drug conjugates (ADCs) [24,25]. Evidence is accumulating to suggest additional mechanisms of action including the formation of intrastrand cross-links [9,10,26] and mono-adducts, the inhibition of transcription factor binding [27,28] and the inhibition of enzymes such as endonucleases [29,30] and RNA polymerase [31].…”
mentioning
confidence: 99%